Acute effect of the ischemic compression technique on the EMG activity of the muscle upper trapezius in subjects with myofascial trigger points - Gelmini, Thomas Ângelo Miguel; Sant’Anna, Patrícia Cilene Freitas; Dhein, William; Torre, Marcelo La (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Myofascial trigger points (MTP) are palpable painful nodules in a shortened area of a given muscle. The ischemic compression technique (IC), which consists of pressing the painful nodule until the elimination of tension or pain, has been shown to be an alternative for the treatment of MTP. The objective of this study was to analyze the influence of the IC technique on the level of pain to the palpation and electrical activity of the right upper trapezius (RUT) muscle during the elevation of the shoulder girdle and abduction of the shoulder in subjects with MTP. Methods: The sample consisted of ten subjects with mean age of 25.9 ± 2.68 years, who performed scapula elevation and right shoulder abduction up to 180º before and after the IC technique on the RUT muscle. The pain level was measured before and after the application of the IC technique and the myoelectric activity during the movements. Data analysis and processing were performed using the BIOMEC-SAS software and were presented in percentage values of the maximum voluntary isometric contraction (%MVIC). Statistical analysis were performed using the Wilcoxon test (α<0.05). Results: There was a significant increase in the mean% of activation (p=0.007) and in the peak %MVIC (p=0.005) of the myoelectric activity of the RUT muscle during the elevation movement of the right scapula. There was also a significant difference in the reduction of the level of pain referred to palpation (p=0.004). There were no differences during abduction movements. The calculation of the effect size showed that the IC technique had great influence on the results found in this study. Conclusion: The IC technique is an important resource for pain modulation and alteration of the myoelectric activity in MTP patients and can be used by physiotherapists when indicated.